2010
DOI: 10.1128/iai.00678-10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the CpxRA Regulon in Haemophilus ducreyi

Abstract: The Haemophilus ducreyi 35000HP genome encodes a homolog of the CpxRA two-component cell envelope stress response system originally characterized in Escherichia coli. CpxR, the cytoplasmic response regulator, was shown previously to be involved in repression of the expression of the lspB-lspA2 operon (M. LabandeiraRey, J. R. Mock, and E. J. Hansen, Infect. Immun. 77:3402-3411, 2009). In the present study, the H. ducreyi CpxR and CpxA proteins were shown to closely resemble those of other well-studied bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
60
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 70 publications
9
60
1
Order By: Relevance
“…Microarray analyses of H. ducreyi and E. coli have shown that Cpx response induction leads to changes in expression of hundreds of genes, including some that are directly regulated by CpxR and many (most) that are not (22,61). Thus, to determine if the above-mentioned genes are bona fide V. cholerae Cpx regulon members and to identify additional candidates that may be regulated indirectly by CpxR, we examined the transcriptional profile of the pandemic strain V. cholerae El Tor C6706 by using a microarray based on the nucleotide sequence of the annotated V. cholerae El Tor strain N16961 (see above).…”
Section: Cholerae Cpxr Regulonmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analyses of H. ducreyi and E. coli have shown that Cpx response induction leads to changes in expression of hundreds of genes, including some that are directly regulated by CpxR and many (most) that are not (22,61). Thus, to determine if the above-mentioned genes are bona fide V. cholerae Cpx regulon members and to identify additional candidates that may be regulated indirectly by CpxR, we examined the transcriptional profile of the pandemic strain V. cholerae El Tor C6706 by using a microarray based on the nucleotide sequence of the annotated V. cholerae El Tor strain N16961 (see above).…”
Section: Cholerae Cpxr Regulonmentioning
confidence: 99%
“…For example, in Haemophilus ducreyi, the Cpx response appears not to be as tightly linked to protein misfolding but rather was shown to control the expression of many genes, including several major virulence determinants, predominantly in a negative fashion (22,23). Similarly, for Vibrio cholerae El Tor N16961, recent evidence indicates that the Cpx pathway may be involved in sensing and mediating adaptation to high salinity in addition to responding to misfolded envelope proteins that contain aberrant disulfide bonds (24).…”
mentioning
confidence: 99%
“…Self-autoagglutination is an indirect indicator of bacterial colonization and virulence in vivo [22,43]. Here, we observed that the autoagglutination ability of the ΔlsgB mutant was significantly decreased, and we also demonstrated a significant attenuation of in vivo pathogenicity, as well as reduced colonization and survival of the ΔlsgB mutant, compared to the wild-type and complementation strains.…”
Section: Discussionmentioning
confidence: 59%
“…Bacterial autoagglutination is a potential virulence-associated indicator in some Gram-negative bacteria [22]; therefore, we next considered whether lsgB gene deletion affects bacterial virulence. In the autoagglutination test, the upper suspension of the static ΔlsgB culture rapidly decreased with time (Figure 4(a)) and most bacteria had precipitated to the bottom of the culture after incubation for 6 h (Figure 4(b)), indicating significantly attenuated autoagglutination of the ΔlsgB mutant compared with the wild-type and C- lsgB strains.
10.1080/21505594.2018.1502606-F0004Figure 4. H. parasuis lsgB deletion attenuates bacterial autoagglutination and pathogenicity, and colonization and survival in vivo .
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation